Association of dietary variety with the risk for dementia: the Yabu cohort study - Yuri Yokoyama; Yu Nofuji; Satoshi Seino; Takumi Abe; Hiroshi Murayama; Miki Narita; Shoji Shinkai; Akihiko Kitamura; Yoshinori Fujiwara (Cambridge University Press, 2023)
Abstract Objective: The consumption of various foods is internationally recommended in healthy diet although the association between dietary variety and incident dementia is unknown. We aimed to examine the association between dietary variety and the incidence of disabling dementia in older Japanese adults. Design: We conducted a prospective cohort study. Dietary variety was assessed based on the Dietary Variety Score (DVS). DVS was assessed by counting the number of ten food components (meat, fish/shellfish, eggs, milk, soyabean products, green/yellow vegetables, potatoes, fruit, seaweed and fats/oils) that were consumed almost daily using a FFQ. Participants were categorised into low (0-2 points), middle (3-4 points) and high (5-10 points) groups based on the DVS. Data on newly diagnosed disabling dementia were retrieved from the public long-term care insurance database. Cox proportional hazards regression was used to estimate hazard ratios (HR) with 95 % CI. Setting: Yabu cohort study, Japan. Participants: A total of 4972 community-dwelling adults aged 65 years or older. Results: During the median follow-up of 6·8 years, 884 participants were newly diagnosed with disabling dementia. After adjusting for confounders, the multivariable-adjusted HR for incident disabling dementia was 0·82 (95 % CI, 0·69, 0·97) for participants in the highest DVS category compared with those in the lowest DVS category (P for trend = 0·019). Conclusions: A higher dietary variety is associated with a reduced risk of disabling dementia in older Japanese adults. These results have potential implications for the development of effective public nutritional approaches to prevent dementia in older adults.